Combustion of Pulverized Biomass Crop Residues and Their Explosion Characteristics. Issue 11 (1st December 2016) - Saeed, Muhammad Azam; Slatter, David J. F.; Andrews, Gordon E.; Phylaktou, Herodotos N.; Gibbs, Bernard M.
ABSTRACT: Two Pakistani crop residues, bagasse (B) and wheat straw (WS), both with high ash content, were milled to <63 µm and the ISO 1 m 3 explosion equipment was used to investigate flame propagation in the dispersed cloud of pulverized biomass. Their turbulent flame speed, pressure rise, and the Kst ( dP / dt max V 1/3 ) were measured and comparison was made with two pulverized coal samples. Minimum explosion concentration (MEC) values for B and WS were in terms of the burned dust mass equivalence ratio (Ø) 0.2Ø to 0.3Ø, which was leaner than for the coal samples. These MEC were in good comparison with those previously determined using the Hartmann explosion tube. Peak turbulent flame speeds were 3.8 m/s for B and 3.0 m/s for WS compared with 3.1–5.2 m/s for the two coal samples. The peak Kst was 103 bar m/s for bagasse and 82 bar m/s for wheat straw and the two coal samples had peak Kst of 78 and 120 bar m/s. The peak rise of pressure relative to ambient atmospheric pressure was measured to be 8.8 bar and 8.5 bar for bagasse and wheat straw, respectively. Overall the agricultural biomass and coal samples had a similar range of reactivity. Thus, these agricultural crop residues are a viable renewable fuel for co-firing with coal or as 100% biofuel operation of steam power plants.